Experimental magic state distillation for fault-tolerant quantum computing - Souza, Alexandre M.; Zhang, Jingfu; Ryan, Colm A.; Laflamme, Raymond (Nature communications, 2011)
Any physical quantum device for quantum information processing (QIP) is subject to errors in implementation. In order to be reliable and efficient, quantum computers will need error-correcting or error-avoiding methods. Fault-tolerance achieved through quantum error correction will be an integral part of quantum computers. Of the many methods that have been discovered to implement it, a highly successful approach has been to use transversal gates and specific initial states. A critical element for its implementation is the availability of high-fidelity initial states, such as |0〉 and the 'magic state'. Here, we report an experiment, performed in a nuclear magnetic resonance (NMR) quantum processor, showing sufficient quantum control to improve the fidelity of imperfect initial magic states by distilling five of them into one with higher fidelity. Error correction in quantum computing can be implemented using transversal gates, which in turn rely on the availability of so-called magic states. The authors experimentally show that it is possible to improve the fidelity of these states by distilling five of them into one.